2002
DOI: 10.1046/j.1365-2648.2002.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Family stress, perceived social support and coping following the diagnosis of a child's congenital heart disease

Abstract: Findings provided evidence for the theoretical and empirical significance of perceived social support as a predictor of family coping. Further, these findings suggest that perceived social support is a factor influencing the resiliency of relatively high-risk groups of families who have a child with chronic illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
152
0
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(166 citation statements)
references
References 41 publications
6
152
0
8
Order By: Relevance
“…The amount of social support and the perceptions of individuals about it seem to play an important mediating and buffering role for stress impact, protecting psychological well-being [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The amount of social support and the perceptions of individuals about it seem to play an important mediating and buffering role for stress impact, protecting psychological well-being [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Jackson and Turnball (2004) cite various studies that point to the importance of social support when a family is dealing with a crisis of this nature. Tak and McCubbin (2002) found that even perceived social support acted as a resiliency factor between family stress and family coping. They further found that family characteristics played an important predicting factor of perceived social support and parental coping.…”
Section: Families and Illnessmentioning
confidence: 98%
“…They found that parents of developmentally disabled children reported more behavior problems, more stress, less well-being and lower community support than families of normally developing children (Nachshen & Minnes, 2005). Tak and McCubbin (2002) used the Resiliency Model to explore social support, stressors and coping in 92 families with children who have congenital heart defects. They found that perceived social support was a resiliency factor between family stress and family coping (Tak & McCubbin, 2002).…”
Section: Major Concepts Of the Theorymentioning
confidence: 99%
“…Tak and McCubbin (2002) used the Resiliency Model to explore social support, stressors and coping in 92 families with children who have congenital heart defects. They found that perceived social support was a resiliency factor between family stress and family coping (Tak & McCubbin, 2002). The following section will provide definitions of each major variable in the model and how it applies to the proposed study.…”
Section: Major Concepts Of the Theorymentioning
confidence: 99%